Already in America: Transnational Homemaking among Liberian Refugees - Trapp, Micah M. (Refuge: Canada’s Journal on Refugees, 2015)
This article explores how refugees at the Buduburam Liberian refugee settlement in Ghana constructed and imagined home in and through a place they have never been to—“America.” Drawing on ethnographic examples of homemaking at Buduburam, this article develops the concept of entanglement to show how preferences for and access to the three durable solutions of the United Nations High Commission for Refugees were influenced by centuries of transnational homemaking embedded in the histories of the transatlantic slave trade and colonization of Liberia. Refugees preferred and practised resettlement not as a final destination, but as an active form of transnationalism. The reconfiguration of homemaking through the lens of entanglement demonstrates the importance of developing migratory policies and practices that are attentive to historic and future forms of inequality.